Evaluation of the collection of the Asian Center Library, University of the Philippines a follow-up study - Cledera, Virgilio Ramel A. (1998)
This study was done to evaluate the collection of the Asian Center Library using the perceptions of the students from the Asian Center and those from other colleges. This study is a follow-up of the study made by Cecilia M. Dizon in 1982, which also evaluated the collection of the Asian Center Library.